Reply to Comments. (March 2013) - Sripada, Chandra; Railton, Peter; Baumeister, Roy F.; Seligman, Martin E. P.
Evidence of prospective processes is increasingly common in psychological research, which suggests the fruitfulness of a theoretical framework for mind and brain built around future orientation. No metaphysics of determinism or indeterminism is presupposed by this framework, nor do considerations of scientific method require determinism—successful scientific theories in the natural sciences all involve probabilistic elements. We speculate that expressive behavior and moral decision making use prospective processes parallel to those used in nonmoral decisions.